PENERAPAN VALUE ENGINEERING PADA PEKERJAAN KONSTRUKSI STUDI KASUS PROYEK PEMBANGUNAN RUMAH SAKIT UMUM PROVINSI SUMATERA SELATAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Palembang is undergoing development in all fields, along with the increasing population, resulting in an increase in the need for public facilities and infrastructure, such as the Palembang Provincial General Hospital Development Project, control and supervision of costs for the project are needed, because project cost control is important One of them is in the process of managing project costs by using the Value Engineering method, with the aim of the government budget being controlled and this research focused on controlling costs in column and beam structure work. The Value Engineering stage starts from making BreakDown Jobs that are associated with the application of Pareto law and making analysis functions and fast diagraming. Cost savings of the South Sumatra Provincial General Hospital Project Construction obtained from the application of Value Engineering to the Column and Beams work costs of Rp. 3,737,843,286 or 7.02%.